Effects of Vermicompost on Quality and Physiological Parameters of Cucumber (Cucumis sativus L.) Seedlings and Plant Productivity - Julė Jankauskienė; Kristina Laužikė; Danguolė Kavaliauskaitė (Horticulturae, 2022)
Cucumbers productivity and fruit quality depend on seedlings’ quality. The success of seedling cultivation largely depends on the choice of a suitable substrate. Therefore the aim of this research is to determine the effect of peat-vermicompost substrates on cucumber seedling quality and crop yield. The research was carried out in a greenhouse covered with double polymeric film in the Institute of Horticulture, Lithuanian Research Centre for Agriculture and Forestry. Cucumber seedlings were grown in different substrates: peat, peat + 10% vermicompost, peat + 20% vermicompost, and peat + 30% vermicompost. The growth of cucumber seedlings in peat and vermicompost substrates was induced. They were 1.9–18.6% taller, and the leaf area of this seedlings was 1.2–1.4 time larger. Furthermore, the fresh leaves mass of these seedlings was 22.7–33.1%, and the fresh root mass was 1.1–1.5 time bigger. The addition of vermicompost to peat substrate has a positive effect on the physiological parameters in the leaves of cucumber seedlings. The total yield of cucumbers grown in peat-vermicompost substrates was 7.4–11.1% higher than that of plants whose seedlings grew in peat substrate.